ChemInform Abstract: 1, 1′‐Sulfinyldipyridinium Bis (Hydrogen Sulfate) Ionic Liquid: Synthesis and Application in the Temperature‐Influenced Synthesis of Novel Pyranopyrimidinediones and Pyranopyrimidinetriones. Issue 15 (April 2015) - Patil, Jayavant D.; Korade, Suyog N.; Pore, Dattaprasad M.
Abstract: At ambient temperature the reaction between 6‐amino uracil (I) and salicylaldehydes in ethanol provides pyranopyrimidinediones [cf.